(untitled) (Research, Society and Development, 2019)
The objective of the research was to determine the relationship between family social climate and aggression in third grade children of the José Joaquín de Olmedo School in Guayaquil - Ecuador. It is descriptive correlational type, not experimental, cross-sectional. The study group was made up of 70 students, enrolled in the 2018 school year. Sampling was non-probabilistic for convenience. The technique of gathering information was the survey. The FES Scale and the AQ questionnaire for aggressiveness were used to measure the family social climate. It was determined that there is a significant inverse relationship between Family Social Climate and Aggressiveness in children (Pearson’s r = -0.426, p: 0.044). The relationships between the subscales of the family relations dimension highlight the role of family cohesion as a limiting element of aggression.